An Analysis of EFL Students’ Speaking Anxiety in 3rd Semester English Education Study Program in State Islamic University of Fatmawati Sukarno Bengkulu Academic Year 2023/2024 - Hidayat, Fadly; Rizal, Syamsul; Efrizal, Dedi (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This study aims to determine the causes of anxiety of English Education Students, semester III when learning to speaking English. This is done because there are still many students who experience anxiety but do not understand what causes anxiety in the students themselves. This research is a qualitative research with data collection method using Observation, Interviews, and Documentation. To analyze the data, the researcher used data triangulation with data reduction, data presentation and drawing conclusions, so that from the data analysis the researcher found that there were three types of anxiety in third semester students majoring in English Education, UIN Fatmawati Sukarno Bengkulu, namely State Anxiety, Trait Anxiety and Specific- Situation Anxiety which if explored the three types of anxiety are caused by communication apprehension, Test Anxiety and Fear of Negative Evaluation. By knowing the causes of student anxiety, it will be easier for teachers and students to find solutions to overcome anxiety when speaking English. Keywords : EFL, Students, Speaking Anxiety